Sustaining Better Life After Retirement: A Pragmatic Approach for University Staff in Ghana - Adongo, Stephany Abokzele (Advances in Social Sciences Research Journal, 2025)
Purpose: This paper explores pragmatic approaches for sustaining a better life after retirement, specifically focusing on university staff in Ghana. It examines current challenges, identifies key strategies, and proposes a framework for effective retirement planning and post-retirement well-being. The study employs a comprehensive review of recent literature, published within the last five years, on retirement planning and post-retirement life quality. It synthesises findings from various sources to develop a pragmatic approach tailored to the Ghanaian university context. The study reveals that effective retirement planning for university staff in Ghana requires a multifaceted approach, encompassing financial planning, health management, social engagement, and continuous learning. Key challenges include inadequate pension schemes, limited financial literacy, and the need for post-retirement career opportunities. This paper recommends actionable strategies for university administrators, policymakers, and individual staff members to enhance retirement preparation and post-retirement life quality. It offers a framework that can be adapted to various institutional contexts within Ghana’s higher education sector.